P(N)BA on AKTV a comparative analysis of PBA on AKTV and NBA TV's network partner, NBA on TNT - Javier, Martin David Lugtu 1992-; Enriquez, Elizabeth L.; University of the Philippines. College of Mass Communication (2013)
"The study is guided by the theory of globalization. It also revolves around the concept of global TV formats as a model of globalization through adaptations, mimicry, localization, etc. This study aims to show how global sports programs influence the local programs through the former's program format. The main texts analyzed and compared are NBA TV (global) and PBA on AKTV (local). The study focuses on two things: (1) Production values and aesthetics or both programs, and (2) the image portrayed by their sportscasters. The analysis of production values focuses on the setting, camera shots and images found in each program. This is coming from an observation that even at a surface level, PBA on AKTV shows a lot of the characteristics of its foreign counterpart. Second, the study analyzes the "repackaged" image of the PBA sportscasters. In order to do this, the researcher analyzes the image and performance of each sportscaster. For image, the researcher focuses on the sportscaster's physical appearance and reputation. Performance, on the other hand, is analyzed through the sportscaster's on-air business and sports knowledge."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Television and sports; Television broadcasting of sports -- Philippines; Video tapes in sports